2016
DOI: 10.1103/physrevb.93.035119
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnon excitation in the field-induced noncollinear ferrimagnetic phase ofBa2Mg2Fe12O22studied by polarized inelastic neutron scattering and terahertz time-domain optical spe

Abstract: We have studied magnetic excitations in a field-induced noncollinear commensurate ferrimagnetic phase of Ba 2 Mg 2 Fe 12 O 22 by means of polarized inelastic neutron scattering (PINS) and terahertz (THz) time-domain optical spectroscopy under magnetic field. A previous THz spectroscopy study reported that the field-induced phase exhibits electric-dipole-active excitations with energies of around 5 meV [Kida et al., Phys. Rev. B 83, 064422 (2011)]. In the present PINS measurements, we observed inelastic scatter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 33 publications
7
21
0
Order By: Relevance
“…A previous THz spectroscopy study by Kida et al has revealed that another Y-type hexaferrite Ba 2 Mg 2 Fe 12 O 22 (BMFO) exhibits electric-field-active magnetic excitation, which is referred to as electromagnon 15,16 . Nakajima et al have recently performed inelastic polarized neutron scattering (IPNS) measurements on BMFO 17 , confirming that the excitation is indeed of magnetic origin and that the magnetic excitation leads to oscillating electric polarization along the c axis via the mangetostriction mechanism.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…A previous THz spectroscopy study by Kida et al has revealed that another Y-type hexaferrite Ba 2 Mg 2 Fe 12 O 22 (BMFO) exhibits electric-field-active magnetic excitation, which is referred to as electromagnon 15,16 . Nakajima et al have recently performed inelastic polarized neutron scattering (IPNS) measurements on BMFO 17 , confirming that the excitation is indeed of magnetic origin and that the magnetic excitation leads to oscillating electric polarization along the c axis via the mangetostriction mechanism.…”
Section: Introductionmentioning
confidence: 95%
“…As mentioned in the introduction, the Y-type hexaferrite BMFO is known to exhibit electromagnon excitation [15][16][17] . Thus, we expect that BSCoFAO also exhibits the electricfield-active magnon excitation, and that it would be applicable for magnetically-tunable light absorption devices working at room temperature.…”
Section: Magnetic Excitations In the Alc Phasementioning
confidence: 99%
See 1 more Smart Citation
“…Note that in both Z-and Y-type hexaferrites, the static polarization P appears due to the inverse Dzyaloshinskii-Moriya interaction 2,8 perpendicularly to the z axis, if one applies an external magnetic field H ⊥ z whereby the transverse conical structure is stabilized. 3,19 However, the magnetic structure of the Y -type hexaferrite is longitudinally conical at µ 0 H = 0 T , 17,18 whereas that of the Z-hexaferrite at zero and small magnetic fields is transverse conical. The electromagnons in both materials share several features: (i) they are active in E ω z even in zero magnetic field, (ii) their frequencies shift with external magnetic field and, finally, (iii) they disappear from the spectra above some threshold magnetic field, when the transverse or longitudinal conical magnetic structures disappear.…”
Section: E Inelastic Neutron Scatteringmentioning
confidence: 99%
“…As regards the hexaferrites, an electromagnon was reported only in the Y -type compound Ba 2 Mg 2 Fe 12 O 22 . [17][18][19] Interestingly, it was observed not only in the spin-induced FE phase below 50 K, but also in the paraelectric one at 90 K, if an external magnetic field (0.4 T ≤ µ 0 H ≤ 1.6 T) was applied ; in that case the magnetic structure changed from proper screw to longitudinal (for H z) or transverse conical (for H ⊥ z). 18 The activation of the electromagnon in E ω z polarized spectra was explained by the exchange striction, although the static electric polarization P⊥ z in hexaferrites comes from the inverse Dzyaloshinskii-Moriya interaction.…”
mentioning
confidence: 99%